PENYUSUNAN MODUL BAHASA INGGRIS DALAM PROGRAM KURSUS GRATIS KABUPATEN BADUNG: PENGABDIAN KOLABORATIF BERSAMA DISDIKPORA KABUPATEN BADUNG, BALI - Desak Putu Eka Pratiwi; I Komang Sulatra (Fakultas Bahasa Asing, 2026)
The free English course program organized by the Disdikpora of Badung Regency represents a strategic effort to improve community communication skills from an early age, particularly in a tourism-based region. This community service activity aims to develop an English learning module tailored to the characteristics of learners at the kindergarten, elementary, and junior high school levels. The program was conducted collaboratively between English Hive and Disdikpora Badung using a participatory approach, which included needs analysis, material design, and module development. Data were collected through observations, interviews with program coordinators and instructors, and identification of learners’ developmental levels and learning needs. The findings indicate that learners require communicative, contextual, and interactive materials adapted to their age levels, such as visual aids, language games, and simple dialogues based on daily situations. Based on these findings, the module was designed using a communicative approach that emphasizes speaking skills and basic language comprehension. Initial implementation showed positive responses from both learners and instructors, as well as increased engagement and confidence in using English. Therefore, the developed module is expected to enhance the effectiveness of the free course program and contribute to improving the quality of English learning for young learners in Badung Regency.